nit-4, a pathway-specific regulatory gene of Neurospora crassa, encodes a protein with a putative binuclear zinc DNA-binding domain. - Yuan, G F (1991)
nit-4, a pathway-specific regulatory gene in the nitrogen circuit of Neurospora crassa, is required for the expression of nit-3 and nit-6, the structural genes which encode nitrate and nitrite reductase, respectively. The complete nucleotide sequence of the nit-4 gene has been determined. The predicted NIT4 protein contains 1,090 amino acids and appears to possess a single Zn(II)2Cys6 binuclear-type zinc finger, which may mediate DNA binding. Site-directed mutagenesis studies demonstrated that cysteine and other conserved amino acid residues in this possible DNA-binding domain are necessary for nit-4 function. A stretch of 27 glutamines, encoded by a CAGCAA repeating sequence, occurs in the C terminus of the NIT4 protein, and a second glutamine-rich domain occurs further upstream. A NIT4 protein deleted for the polyglutamine region was still functional in vivo. However, nit-4 function was abolished when both the polyglutamine region and the glutamine-rich domain were deleted, suggesting that the glutamine-rich domain might function in transcriptional activation. The homologous regulatory gene from Aspergillus nidulans, nirA, encodes a protein whose amino-terminal half has approximately 60% amino acid identity with NIT4 but whose carboxy terminus is completely different. A hybrid nit-4-nirA gene was constructed and found to function in N. crassa.